Cyclosporine A or intravenous cyclophosphamide for lupus nephritis: the Cyclofa-Lune study - Zavada, J; Pesickova, Ss; Rysava, R; Olejarova, M; Horák, P; Hrncír, Z; Rychlík, I; Havrda, M; Vítova, J; Lukác, J; Rovensky, J; Tegzova, D; et al. (Lupus, 2010)
Intravenous cyclophosphamide is considered to be the standard of care for the treatment of proliferative lupus nephritis. However, its use is limited by potentially severe toxic effects. Cyclosporine A has been suggested to be an efficient and safe treatment alternative to cyclophosphamide. Forty patients with clinically active proliferative lupus nephritis were randomly assigned to one of two sequential induction and maintenance treatment regimens based either on cyclophosphamide or Cyclosporine A. The primary outcomes were remission (defined as normal urinary sediment, proteinuria <0.3 g/24 h, and stable s-creatinine) and response to therapy (defined as stable s-creatinine, 50% reduction in proteinuria, and either normalization of urinary sediment or significant improvement in C3) at the end of induction and maintenance phase. Secondary outcomes were incidence of adverse events, and relapse-free survival. At the end of the induction phase, 24% of the 21 patients treated by cyclophosphamide achieved remission, and 52% achieved response, as compared with 26% and 43%, respectively of the 19 patients treated by the Cyclosporine A. At the end of the maintenance phase, 14% of patients in cyclophosphamide group, and 37% in Cyclosporine A group had remission, and 38% and 58% respectively response. Treatment with Cyclosporine A was associated with transient increase in blood pressure and reversible decrease in glomerular filtration rate. There was no significant difference in median relapse-free survival. In conclusion, Cyclosporine A was as effective as cyclophosphamide in the trial of sequential induction and maintenance treatment in patients with proliferative lupus nephritis and preserved renal function.(ClinicalTrials.gov identifier: NCT00976300)
Keywords: výsledek terapie; Young Adult; nefritida při lupus erythematodes; Infusions, Intravenous; Male; intravenózní infuze; Immunosuppressive Agents; Survival Rate; mladý dospělý; Lupus Nephritis; Cyclophosphamide; Adult; dospělí; mužské pohlaví; Kidney Function Tests; Treatment Outcome; lidé; ženské pohlaví; Humans; Cyclosporine; cyklofosfamid; vyšetření funkce ledvin; cyklosporin; Female; míra přežití; imunosupresiva